KAJIAN TOPONIMI PENAMAAN TEMPAT DI TAMAN NASIONAL DANAU SENTARUM KABUPATEN KAPUAS HULU - Roni Roni; Ahmad Rabi’ul Muzammil; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The problem in this study is how the process of naming places inDanau Sentarum National Park, Kapuas Hulu Regency. Toponymycategorization based on aspects and types of place naming andimplementation of the Toponymy Study of Place Naming in DanauSentarum National Park, Kapuas Hulu Regency as a supplement toIndonesian language learning text material 2013 Curriculum. Themethod used in this research is the method of observation, proficientmethod, and descriptive method. The form of this research is a form ofqualitative research. Sources of data in this study are informants whoare people who live in the Danau Sentarum area and have known thebasis for naming places in Danau Sentarum National Park itself. Thetechniques used by researchers in collecting data in the field arefishing rod techniques, face-to-face conversation techniques, notetaking techniques, and recording techniques. Based on the overallresults of the research with the scope of research based on the field ofmanagement of the Batang Lupar area, there are 9 place names,including 3 islands, 4 bottom, 1 lake and 1 river. This research isrelated to the 2013 Curriculum for Indonesian language subjects inSMP class VII Odd semesters which are suggested to be a referencefor contextual text materials for teaching and learning activities inschools.